2013
DOI: 10.1007/s00268-013-2315-z
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Intraoperative Distractions on Patient Safety: A Prospective Descriptive Study Using Validated Instruments

Abstract: Distractions are prevalent in ORs and in this study were linked to deterioration in intraoperative patient safety checks. Surgeons should be mindful of their tolerance to distractions. Surgical leadership can help control distractions and reduce their potential impact on patient safety and performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
84
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 72 publications
(87 citation statements)
references
References 35 publications
3
84
0
Order By: Relevance
“…NOTECHS scores correlated inversely with ‘glitch rate’, whereas OTAS scores inversely correlated with the impact of distractions6 10. NOTSS and the Cannon‐Bowers scale correlated well with each other40 46, 48.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…NOTECHS scores correlated inversely with ‘glitch rate’, whereas OTAS scores inversely correlated with the impact of distractions6 10. NOTSS and the Cannon‐Bowers scale correlated well with each other40 46, 48.…”
Section: Resultsmentioning
confidence: 91%
“…In addition to surgeons' technical proficiency, non‐technical skills have been implicated in clinical outcomes after surgery and operating theatre efficiency. These non‐technical skills include, in addition to teamwork, attitudes towards safety, situational awareness, decision‐making, communication and theatre environment1, 2, 3, 4, 5, 6, 7, 8, 9, 10. This review was designed to focus on teamwork.…”
Section: Introductionmentioning
confidence: 99%
“…In one observational study, up to 39 events (distractions or interruptions, such as doors opening, phones/bleeps going off, irrelevant communication, etc.) were observed in a single case [4].…”
Section: Introductionmentioning
confidence: 76%
“…Observational studies [4,5] have tried to determine the effect of distraction on surgical outcomes. In an analysis of events reported via Pennsylvania Patient Report System in the period between January 2011 and May 2013 [6], 304 procedure problems were found in which distraction had played a contributing part.…”
Section: Discussionmentioning
confidence: 99%
“…Emerging evidence of the prevalence of opportunity for error in the OR related to these factors has sparked research into decreasing chances for preventable harm, increasing patient safety, and improving surgical outcomes. [3][4][5][6][7] Halverson et al 3 classified communication breakdowns in the OR by type, subject, and effect. They identified 66 communication failures over a 150-hour period and observed that most communication errors were related to surgical equipment.…”
mentioning
confidence: 99%